Up-regulated miR-133a orchestrates epithelial-mesenchymal transition of airway epithelial cells. Issue 1 (December 2018) - Chen, Linjie; He, Xiaobai; Xie, Yan; Huang, Yapei; Wolff, Dennis; Abel, Peter; Tu, Yaping
Abstract Dysregulation of microRNAs (miRNAs) contributes to epithelial-mesenchymal transition (EMT) of cancer, but the pathological roles of miRNAs in airway EMT of lung diseases remains largely unknown. We performed sequencing and real-time PCR analysis of the miRNA expression profile of human airway epithelial cells undergoing EMT, and revealed miR-133a to be one of the most common up-regulated miRNAs. MiR-133a was previously reported to be persistently up-regulated in airway epithelial cells of smokers. We found that mice exposed to cigarette smoke (CS) showed airway hyper-responsiveness, a typical symptom occurring in CS-related lung diseases, up-regulation of miR-133a and EMT marker protein N-cadherin in airway epithelium. Importantly, miR-133a overexpression induces airway epithelial cells to undergo spontaneous EMT via down-regulation of grainyhead-like 2 (GRHL2), an epithelial specific transcriptional factor. Loss of GRHL2 causes down-regulation of epithelial splicing regulatory protein 1 (ESRP1), a central coordinator of alternative splicing processes that are critical in the regulation of EMT. Down-regulation of ESRP1 induces isoform switching of adherens junction-associated protein p120-catenin, and leads to the loss of E-cadherin. Our study is the first to demonstrate that up-regulated miR-133a orchestrates airway EMT via alternative splicing processes, which points to novel therapeutic possibilities for the treatment of CS-related lung disease.